Stamping the vaccine passport? Public support for lifting COVID-19 related restrictions for vaccinated citizens in France, Germany, and Sweden. Issue 38 (9th September 2022) - Stoeckel, Florian; Stöckli, Sabrina; Phillips, Joseph; Lyons, Benjamin; Mérola, Vittorio; Barnfield, Matthew; Szewach, Paula; Thompson, Jack; Reifler, Jason
Abstract: During the COVID-19 pandemic, many countries implemented restrictions to limit the spread of the SARS-CoV-2 virus (e.g. travel restrictions and lockdowns). One path to loosening restrictions is to do so selectively only for vaccinated individuals (e.g. by implementing vaccine passports domestically or as a prerequisite for international travel). Setting different rules based on people's vaccination status is however a contentious issue among health policy experts, government officials, and the public. Our analysis focuses on the levels and correlates of public support for the lifting of restrictions for the vaccinated in April 2021, i.e. at a time when restrictions were in place and a selective lifting of these restrictions just for the vaccinated was debated in Europe. We use representative quota samples of the populations of France (N = 1, 752), Germany (N = 1, 759), and Sweden (N = 1, 754). We find that a slight plurality support lifting restrictions for the vaccinated in France and Germany but not in Sweden. Vaccine hesitancy emerges as strong predictor of opposition to such a policy. Additionally, individuals who are already vaccinated (in France and Germany) and who are higher in risk-seeking express more support for the lifting of restrictions for the vaccinated. We discuss implications for the debate on vaccine passports.